Identifikasi Jenis Bangun Datar dengan Algoritma Line Hough Transform dan Circular Hough Transform - Eflin Winata; Helvi Risna; Renni Angreni (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2016)
Two-dimensional figure is consisted of straight and curved lines, which is needed a special method to identify them. The methods that can be used are called Line Hough Transform for identifying straight line and Circular Hough Transform to identifying curved line. This research is to apply this algorithm, Line Hough Transform and Circular Hough Transform, in identifying two-dimensional figure by using an application as a supported testing media. The types of two-dimentional figure, that are used in this study, are square, rectangle, trapezium, triangle, parallelogram, kite rhombus, and circle. Based on test results using 20 types of testing data each type two-dimensional figure shows the percentage of success in identifying twodimensional figure is 87.5%. Many factors affect the rate of successful Identification of twodimensional figure as size, angle, threshold, and how to draw normal.